STUDI EKOLOGI PENGOLAHAN GARAM TRADISIONAL KABUREA BERBASIS KEARIFAN LOKAL DI DESA TENDAKINDE, FLORES - Sena, Hermina; Sudiana Mahendra, Made; Suarna, I Wayan (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science); Vol 17 No 1 (2023), 2023)
Tendakinde Village is a village located in Nagekeo Regency, and has coastal resources, namely traditional salt production. Knowledge in processing patterns is quite extensive, as to be able to make salt production a regional icon, a strategy is needed that can process natural resources properly. The purpose of this study is to examine traditional Kaburea salt processing techniques based on local wisdom, to determine the impact of climate change on salt production, to understand and develop strategies for the existence of traditional Kaburea salt processing. Data collected through literature, observation, focus group discussion with 15 participants, interviews with 8 informants, and questionnaires. The sample used in the questionnaire is 30 samples. The data obtained is then processed using the IFE matrix, EFE matrix, and SWOT analysis. Traditional salt processing is shown in the process of preparation to production of salt through rules which then become a habit (local wisdom). The basic materials for the facilities used are wood and bamboo, then the raw materials for salt production are sea water which is collected in wells. However, climate change is a bad influence on the quality of salt, therefore it is necessary to work together from the government and Kaburea salt farmers in permanently repairing the embankment. The results of the analysis of the IFE matrix and the EFE matrix show that Kaburea's traditional salt processing is in a grow and build position, meaning that the development of the salt business must be maintained amidst its growth rate. Based on the results of the SWOT analysis, 12 alternative strategies were obtained that the Kaburea salt farmers were expected to be able to implement strategies according to their abilities and circumstances. Keywords: Ecology; Local Wisdom; Traditional Salt; Strategy